BUILDING MODEL OF CORPORATE CULTURE BASED ON BASIC VALUES OF STATE DEFENSE TOWARDS STATE UNIVERSITY BASED ON FINANCIAL MANAGEMENT-PUBLIC SERVICE AGENCY (PK-BLU) UPN "VETERAN" YOGYAKARTA - Hastho Joko Nur Utomo; Asep Saepudin; Kurnia Arofah (Jurnal Pertahanan & Bela Negara, 2020)
This article is the result of institutional research on building model of corporate culture of UPN "Veteran" Yogyakarta based on Basic Values of State Defense towards State University Based on Financial Management-Public Service Ageny (PTN PK-BLU. This research belongs to the descriptive research. Data was collected through distributing questionnaires to 195 respondents and focus group discussions (FGD). The results of the research explained that in general, based on the characteristics of UPN "Veteran" Yogyakarta as a state university characterized by State Defense, there needs to be strengthening or development of a new corporate culture at UPN "Veteran" Yogyakarta based on the basic values of state defense towards PTN PK-BLU. Corporate culture that needs to be built is Discipline, Struggle, Creativity, Excellence, love for Homeland, Consciousness of have a nation and state, Convinced of Pancasila as the Foundation of the State, Willing to Sacrifice for the Nation and state, possessing initial ability for the state defense, Honesty and Integrity, Learner, and Upholding Meritocracy. To build this culture, there are a number of effort that need to be carried out, namely: involving stakeholders in formulating corporate culture, massive socialization, budgetary support in upholding the corporate culture, sustainable monitoring and evaluation, and building information, and reward and punishment system, which supports the emergence of a new corporate culture.Keywords: corporate culture, Basic Values of state defense